Improving The Hospital Waste Management: An Action Research Study at The UMY Dental Hospital - Pipiet Okti Kusumastiwi; Siti Jauza Hanan (YCAB Publisher, 2026)
Background: Hospital waste as an inherent part of human life is one of the most serious issues affecting public health and the environment. Objective: This study aims to improve hospital waste management at the UMY Dental Hospital. Methods: This is an action research study using Simmons model. First, a list of critical issue was identified during the waste management process through a standard checklist and discussion with hospital officials and staff. A prioritizing matrix was utilized to rank the issues that were identified. Eleven interventions were then planned and carried out over a six-month period following consultation with hospital personnel. The performance of waste management was then reassessed. Results: The participants' average understanding of hospital waste management (HWM) standards increased significantly (from 64 ± 13.8 before to the training to 84.6 ± 20.6). The production of general waste decreased by 24.89% in terms of waste weight (99.2 kg–74.5 kg) and 27.7% in terms of rubbish bags. The amount of infectious waste produced decreased by 32.09% in terms of trash weight (58.9 kg–40 kg) and by 22.8% in terms of garbage bag count. The number of goods that met the HWM requirements increased from 16 to 32. Conclusion : Training, provision of guidelines, SOP, and educational posters, and development and implementation of hospital waste management program can improve waste management at the UMY Dental Hospital by augmenting awareness of medical waste management, elevating compliance with medical waste management standards, and decreasing the volume of hospital waste produced.